Biodegradation characteristics of patulin by Saccharomyces cerevisiae during fermentation. (March 2023) - Yang, Chao; Peng, Bangzhu
Abstract: Patulin is a mycotoxin that contaminates apple-based products and poses a serious threat to human health. Saccharomyces cerevisiae can efficiently degrade PAT during fermentation. However, the degradation mechanism of PAT remained unclear. This study investigated the degradation of PAT by S. cerevisiae and the formation of degradation products. The results showed that 20 μg/mL of PAT was completely degraded by S. cerevisiae at 5 d of fermentation, and cycloheximide inhibited the degradation process. Both extracellular and intracellular enzymes can degrade PAT, but the latter had a higher degradation capacity. PAT exhibited the highest induction capacity of intracellular enzymes at 2 d, which was a 6.52% higher degradation rate than the uninduced. Additionally, PAT was firstly degraded to Z-ascladiol and then further to E-ascladiol by intracellular enzymes. The findings provide new insights into the biodegradation mechanism of PAT and a theoretical basis for removing methods of PAT contamination in apple-based products. Highlights: S. cerevisiae completely degraded 20 μg/mL PAT at 5 d. The intracellular enzymes of S. cerevisiae mainly degraded PAT. PAT induced the degradation capacity of S. cerevisiae. PAT was first degraded to Z-ascladiol and then to E-ascladiol by intracellular enzymes.